IBN KHALDUN THOUGHT: A review of al-Muqaddimah Book - Wawan Hernawan (Jurnal Ushuluddin, 2015)
Nowadays Muslim and non-Muslim scholar have no paid exhaustion attention yet onal- Muqaddimah book of Ibn Khaldun (1332-1406). Al-Muqaddimah Book is still being studied and debated critically. Actually, this work is still “dazzling” social scientists, anthropologists, theologians, philosophers, historians, and economists even compared with the other great works produced by other classical Muslim scholars. Search for the book of al-Muqaddimah Ibn Khaldun intends to seek and drank authenticity thoughts. It becomes important in the center of issue. We should be wise to this Muslim leader, because it has a big hand in an attempt to find the “authenticity” of Muslim thought. By using the method of historical research, it is obtained: first,for Ibn Khaldun, history is one of the disciplines studied extensively by the nations and generations. Second, the legal history is applicable universally so the truth can be revealed. Third, a historian should study the areas of human life (sociology, anthropology, theology, philosophy, history, and economics) to determine differences between main and general characteristics. Fourth, related to the modern social sciences, undoubtedly Ibn Khaldun is first beginning of sciences. He was a golden bridge for the development of science and the history of modern sociology